Weakened PAM/PEI Polymer Gel for Oilfield Water Control: Remedy with Silica Nanoparticles - Amir, Z. (MDPI, 2022)
Polymer gel treatment is one of the most popular conformance control methods used in the petroleum industry. The advantage of the polymer gel system used in harsh reservoir conditions is an integrated process that must take into account all elements of gelation kinetics. In high-temperature applications, NH4Cl has been selected as a retarder to extend the gelation time of a PAM/PEI gel system. However, the gel network loses gel strength when salt and retarder increase, resulting in a weak gel structure, and becomes susceptible. The combination of these two variables leads to the development of a weak gel network, making it fragile and susceptible. To strengthen the weakened PAM/PEI polymer gel, the addition of silica nanoparticles (silica NP) is considered an effective remedy. This article presents the performance of PAM/PEI polymer gel strengthened with silica NP, especially the performance in terms of viscosity, gelation time, and gel strength, as well as performance in porous media. For example, the results exhibited a high storage modulus, Gâ², which is almost 800 Pa, compared to the loss modulus, Gâ²â², throughout the frequency and strain range, indicating solid-like behavior, at significantly high amounts of silica NP. This finding provides a better understanding and knowledge on the influence of solid particles in enhancing the performance of PAM/PEI polymer gel that has been weakened by salinity and retarder. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.